Effect of Regular Aerobic Training on Serum C-Reactive Protein and IL-6 Levels in Obese Women - Özdemir, Çigdem; Özgünen, Kerem; Günasti, Özgür; Coskun Özyol, Funda; Kurdak, S. Sadi (Puerto Rico Health Sciences Journal, 2021)
Objective: This study’s objective was to evaluate interleukin-6 (IL-6) and C-reactive protein (CRP) responses and performance changes in obese women after 8 weeks of aerobic training with an intensity of 50 to 60% of their individual maximum oxygen uptake (VO2). Methods: A total of 18 sedentary women with an average age of 44.3 (± 1.9) years volunteered for this study. Over a period of 8 weeks, in 4 40-minute sessions per week, the participants walked at an exercise intensity that caused their heart rates to increase to levels corresponding to 50 to 60% of their VO2 peaks. Blood samples were collected from the participants, both when they were at rest and a couple of minutes after the end of the 1st exercise session. Sampling was repeated in the 4th and 8th weeks, before and after the last training sessions. Results: The participants’ body mass indices and weights decreased significantly by the end of the 8th week, while their maximum running speeds and VO2 peaks increased significantly. There were no differences in CRP or IL- 6 concentrations between the pre- and post-training sessions, but most of the participants’ IL-6 levels dropped below 10 pg/ml after 8 weeks of training. Conclusion: Although no significant changes were observed in CRP or IL-6 concentrations, it is important to note that in response to aerobic training, the IL-6 levels of most of the participants fell to what is generally considered acceptable.